Answer:
whenever you're multiplying terms that have exponents you multiply the coefficients and add their exponents:
Step-by-step explanation:
I think the answer to your first question should be:
30a²b - 30ab²
Your second answer is good
for example, 6a²b³c x 2abc = 6(2)(a²)(a)(b³)(b)(c)(c)
= 12a³b⁴c²
If you're asking how, here's an example
A standard form equation is when it is set up.
Ax + By = C.
6x + 2y = 4.
A slope-intercept form equation is when it is set up y=mx+b.
Y = - 3x + 2.
4y = -8x + 16 then divide all by 4.
y = -2x + 4 slope form.
The answer is 132.